(untitled) (Faculty of Education Scientific Journal, 2024)
Today’s world demands scientific inquiry, which goes beyond the study of natural phenomena to encompass human phenomena linked to a range of social, psychological, educational, and economic domains. Additionally, a proposed plan for a training program aimed at equipping second cycle students in the Sultanate of Oman with research abilities will be presented. The study’s proposed training program to improve the research abilities of second cycle students in the Sultanate of Oman was developed as its conclusion.